Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1097/00000542-199906000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combined Mouth Closure and Chin Lift on Upper Airway Dimensions during Routine Magnetic Resonance Imaging in Pediatric Patients Sedated with Propofol

Abstract: This study shows that all children had a preserved upper airway at all measured sites during propofol sedation. Chin lift caused a widening of the entire pharyngeal airway that was most pronounced between the tip of the epiglottis and the posterior pharyngeal wall. In pediatric patients, chin lift may be used as a standard procedure during propofol sedation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 25 publications
1
36
0
1
Order By: Relevance
“…This explanation is supported by PICKERING and BEARDSMORE [18] who showed that when the chin lift manoeuvre was performed with an almost closed mouth in children with adenotonsillar hypertrophy, there was greater resistance to nasal breathing, caused by the adenoids. However, in a previous study it was demonstrated that in healthy children without adenotonsillar hypertrophy, chin lift is an effective manoeuvre to insure an open airway during propofol anaesthesia [19]. Chin lift widened the airway diameter anterioposteriorly mainly at the area of the epiglottis and transversally at the soft palate [19].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This explanation is supported by PICKERING and BEARDSMORE [18] who showed that when the chin lift manoeuvre was performed with an almost closed mouth in children with adenotonsillar hypertrophy, there was greater resistance to nasal breathing, caused by the adenoids. However, in a previous study it was demonstrated that in healthy children without adenotonsillar hypertrophy, chin lift is an effective manoeuvre to insure an open airway during propofol anaesthesia [19]. Chin lift widened the airway diameter anterioposteriorly mainly at the area of the epiglottis and transversally at the soft palate [19].…”
Section: Discussionmentioning
confidence: 98%
“…However, in a previous study it was demonstrated that in healthy children without adenotonsillar hypertrophy, chin lift is an effective manoeuvre to insure an open airway during propofol anaesthesia [19]. Chin lift widened the airway diameter anterioposteriorly mainly at the area of the epiglottis and transversally at the soft palate [19].…”
Section: Discussionmentioning
confidence: 98%
“…Different mechanisms may explain the observed increases in TGV with blood loss. The thoracic blood volume can considerably decrease as a result of acute hemorrhage (30). This decrease can contribute to the increase in TGV by the replacement of blood by gas in the thoracic cavity.…”
Section: Discussionmentioning
confidence: 99%
“…18 In addition, chin lift, thrusting the jaw forward or extension of the head also widens the oropharyngeal space. 19,20 In our patients, during the manual in-line position, it was often difficult to advance the fibrescope through the space between the epiglottis and posterior pharyngeal wall, and it was possible to insert the fibrescope into the trachea within two minutes in only eight of 20 patients.…”
Section: Discussionmentioning
confidence: 82%